Inhibiting amyloid β‐protein assembly: Size–activity relationships among grape seed‐derived polyphenols. (2nd September 2015) - Hayden, Eric Y.; Yamin, Ghiam; Beroukhim, Shiela; Chen, Benson; Kibalchenko, Mikhail; Jiang, Lin; Ho, Lap; Wang, Jun; Pasinetti, Giulio M.; Teplow, David B.
Abstract Epidemiological evidence that red wine consumption negatively correlates with risk of Alzheimer's disease has led to experimental studies demonstrating that grape seed extracts inhibit the aggregation and oligomerization of Aβ in vitro and ameliorate neuropathology and behavioral deficits in a mouse model of Alzheimer's disease. The active agent in the extracts is a mixed population of polyphenolic compounds. To evaluate the relative potency of each of these compounds, HPLC was used to fractionate the mixture into monomers, dimers, and oligomers. Each fraction was analyzed for its effect on Aβ conformational dynamics (circular dichroism), oligomerization (zero‐length photochemical cross‐linking), aggregation kinetics (Thioflavin T fluorescence), and morphology (electron microscopy). The relative activities of each fraction were determined on the basis of molar concentration (mol/L) or mass concentration (g/L). When molar concentration, the number concentration of each polyphenolic compound, was considered, the oligomer fraction was the most potent inhibitor of Aβ oligomerization and aggregation. However, when mass concentration, the number concentration of phenolic groups, was considered, monomers were the most potent inhibitors. To understand these ostensibly contradictory results, a model of polyphenol:Aβ complexation was developed. This model, which was found to be consistent with published X‐ray crystallographic studies, offers an explanation for the effects of functional group polyvalency on inhibitor activity. Our data emphasize the importance of an in‐depth understanding of the mechanism(s) underlying 'concentration dependence' in inhibitor systems involving polyfunctional agents. <boxed-text content-type="graphic" id="jnc13270-blkfxd-0002" position="anchor" orientation="portrait"> </boxed-text>Grape seed polyphenolic extracts have been shown to inhibit the aggregation of Aβ in vitro and to ameliorate neuropathology and behavioral deficits in a mouse model of AD. The active agent in the extracts is a mixed population of polyphenolic compounds, including monomers, dimers, and oligomers. We found that monomers were the most potent inhibitors, when the number concentration of phenolic groups was considered. We developed a model of polyphenol:Aβ complexation that offers an explanation for the effects of functional group polyvalency on inhibitor activity. Our data emphasize the importance of an in‐depth understanding of the mechanism(s) underlying 'concentration dependence' in inhibitor systems involving polyfunctional agents.